Analysis of rail rates for wheat rail transportation in Montana; comparing rates in a captive market to one with more intramodal competition - McKamey, Matthew (Kansas State University, 2009)
Today’s rail industry is the outcome of years of regulatory and technological change. Since the passage of the Staggers Rail Act of 1980 the industry has seen consolidation through mergers and acquisitions. The rail industry in Montana has a rich rail history that includes the completion of a northern east-west route over 100 years ago that provided a commerce route from the interior of the US heartland to the ocean ports in the Pacific Northwest. In those hundred years the rail traffic across Montana has seen dramatic change. In the past, those routes have provided access for Montana freight; today those routes primarily serve the needs of consumers and industries far beyond Montana. While the state’s economy is primarily agricultural, the largest user of rail transportation is the energy industry. This leaves the agriculture industry with a lower priority for access, providing a quandary for rail service for the grain industry in the state. In a state where more than eight national and regional rail carriers once operated, Montana is now only serviced by a small handful, one of which operates over 80% of the rail miles within its borders. Furthermore that carrier provides service through those regions that are almost strictly agricultural, needing the greatest access to the most cost effective means of transportation for the bulk movement of grain. The objectives of this thesis are to develop a model to measure railroad costs and competition; determine the principal cost determinants and measure intramodal competition by comparing the rates in a captive market (Montana) to one with more intramodal competition (Kansas).
Keywords: Railroad Wheat Prices; Montana Railroads; Kansas Railroads; Railroad Competition; Agriculture, General (0473); Economics, Agricultural (0503); Transportation (0709)